Cnn1 inhibits the interactions between the KMN complexes of the yeast kinetochore - Bock, Lucy J.; Pagliuca, Cinzia; Kobayashi, Norihiko; Grove, Ryan A.; Oku, Yusuke; Shrestha, Kriti; Alfieri, Claudio; Golfieri, Cristina; Oldani, Amanda; Dal Maschio, Marianna; Bermejo, Rodrigo; Hazbun, Tony R.; et al. (Nature cell biology, 2012)
Kinetochores attach the replicated chromosomes to the mitotic spindle and orchestrate their transmission to the daughter cells. Kinetochore–spindle binding and chromosome segregation are mediated by the multi-copy KNL1 Spc105 , MIS12 Mtw1 and NDC80 Ndc80 complexes that form the so-called KMN network. KMN–spindle attachment is regulated by the Aurora B Ipl1 and MPS1 Mps1 kinases. It is unclear whether other mechanisms exist that support KMN activity during the cell cycle. Using budding yeast, we show that kinetochore protein Cnn1 localizes to the base of the Ndc80 complex and promotes a functionally competent configuration of the KMN network. Cnn1 regulates KMN activity in a spatiotemporal manner by inhibiting the interaction between its complexes. Cnn1 activity peaks in anaphase and is driven by the Cdc28, Mps1 and Ipl1 kinases. The kinetochore is a multiprotein complex that tethers chromosomes to the mitotic spindle for accurate chromosome segregation. De Wulf and colleagues now show in budding yeast that the protein Cnn1 functions at the kinetochore and is recruited to the inner kinetochore, in a manner dependent on its phosphorylation mediated by the Cdc28, Mps1 and Ipl1 kinases.